Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/2041669520987254
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Bar Graph Averages: Overcoming Within-the-Bar Bias

Abstract: Although most people are not aware of it, bias can occur when interpreting graphs. Within-the-bar bias describes a misinterpretation of the distribution of data underlying bar graphs that indicate an average or where the average estimation point moves inside the bar when the average of several graphs is estimated. This study proposes and tests two methods based on information processing to reduce within-the-bar bias. The first method facilitates bottom-up processing by changing various graph features, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Okan and colleagues ( 2018 ) also replicated both the core asymmetry (this time using health data) and the finding that nonbar graphs did not produce the effect; they additionally found that the asymmetry, counterintuitively, increased with graph literacy. Finally, Godau, Vogelgesang, and Gaschler (2016) and Kang and colleagues ( 2021 ) showed that the asymmetry remains in aggregate—carrying through to judgments of the grand mean of multiple bars.…”
Section: Related Workmentioning
confidence: 97%
“…Okan and colleagues ( 2018 ) also replicated both the core asymmetry (this time using health data) and the finding that nonbar graphs did not produce the effect; they additionally found that the asymmetry, counterintuitively, increased with graph literacy. Finally, Godau, Vogelgesang, and Gaschler (2016) and Kang and colleagues ( 2021 ) showed that the asymmetry remains in aggregate—carrying through to judgments of the grand mean of multiple bars.…”
Section: Related Workmentioning
confidence: 97%